PENGUNAAN BAHASA TERNATE DALAM SASTRA LISAN DAN ACARA RITUAL KEAGAMAAN - Karim, Kodrat Hi; Hasim, Rustam (JURNAL ILMU BUDAYA, 2018)
This paper describes types of phrases expressed in Ternate oral literature. As various types of Indonesian literature, it is also found that oral literature of Ternate consists of many different forms and type, this variety can be classified into different classification such as based on the period of before and after the establishment of Islamic teaching in this area. Ternate oral literature has a close relationship with the tradition of its society such as its ethics, social and economic life both internally and externally. Oral tradition in the sultanate of Ternate is a set of habits and behaviors of daily life inherited from generation to generation. Before the introduction of Islam which is known as the period ofmomoleperiod, this country already has a number of oral traditions that includes cultural values, customs, community systems and belief systems.In line with the development of Ternate language into lingua-france in North Maluku, Ternate literature then became the property of the community as North Maluku. Even it expands spreading alongside the development of the power of the Sultanate of Ternate from XV to XVII century. It is no wonder that if the oral literature is influenced by local languages as well as Malay, Arabic and Javanese languages.